Influence of Induced Soil Compaction on the Growth, the Yield and the Soil Loss Resulting from the Groundnut Harvesting - Ewetola, Esther Abosede (JOURNAL OF TROPICAL SOILS, 2020)
The research was conducted to study the growth and the yield of the groundnut plant and to quantify the soil loss after groundnut harvesting as influenced by induced soil compaction. A ten kilogram of soil was packed in the pots with an initial bulk density of 1.05 Mg m-3, then it were compressed to1.57, 1.72, 1.88, 2.04, and 2.42 Mg m-3. The research was conducted in a completely randomized design with three replications. Groundnut seeds were sown in pots and the plant growth data were collected in a 2-week interval while force and energy of harvesting and soil loss due to groundnut harvesting were determined at 12 weeks after sowing. Data were analyzed using ANOVA and Fishers LSD at P= 0.05. Soil compacted to1.88 Mgm-3 produced more taller plant, more higher number of leaves and branches than control. Soil compaction significantly reduced the number of pods, roots, and fresh root weight compared to control. Bulk density (2.04 Mgm-3) required a significantly higher force (42.47 N) and energy (45.73 J) in harvesting than control and other compaction levels. Soil loss due to the groundnut harvesting increased (13- 42%) in all compaction levels although statistically not different. Soil compaction beyond 1.88 Mg m-3 could affect the growth and the yield of groundnut and could increase the soil loss at harvesting.